Analysis of Hydrocolloids in Crystalline Material. Issue 7 (12th May 2017) - Herfurth, Julia; Ulrich, Joachim
Abstract: Additives in foods are a commonly applied tool to optimize the product in terms of appearance, handling, quality, and production process. Such additives are ingredients which can change, e.g., the texture within the product and can also influence other main components in a formulation. It is demonstrated that the use of hydrocolloids as texturants in sweets influences the layer formation of crystallized sucrose for coating purposes. An incorporation of hydrocolloids in the crystalline materials changes the storage stability since the produced coated gels lose water, the so‐called syneresis. It is necessary to achieve a pure crystallized sugar layer and, therefore, to develop a tool to control the production process. A successful analysis of hydrocolloids, e.g., of gelatin, agar or carrageenans, in crystallized sucrose was performed by means of precipitation and coloring methods. Abstract : The analysis of gelatin, agar, or carrageenans in crystallized sucrose is an important method to estimate the effects of hydrocolloids on crystallized coated products. An incorporation of these texturants can lead to product changes like storage stability, layer thicknesses, and mouth feeling. All hydrocolloids are incorporated into the coating material during layer formation of coated sweets.